Bringing it back from Mexico: Eleven paintings of trees in I cinque libri delle piante of Pier'Antonio Michiel (1510–1576). (18th January 2019) - Mason, Peter; Pardo-Tomás, José
Abstract: I cinque libri delle piante of Pier'Antonio Michiel (1510–1576) are kept in the Biblioteca Marciana in Venice. Eleven of the 1, 028 plant drawings contained in their five volumes stand out for their notable stylistic differences from the rest. The authors advance the hypothesis that these eleven drawings derive from the work of indigenous scribe-artists in the Valley of Mexico. In tracing the various series of copies of them that circulated between New Spain, the Iberian peninsula and Italy, they highlight the important role played in the production and transportation of copies by Marcantonio Da Mula (1506–1572), and suggest the Spanish nobleman Diego Hurtado de Mendoza (c.1503–1575) as the link between the Spanish court and Michiel's native Venice.